2020
DOI: 10.1186/s41232-020-00137-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral sterile inflammation in neurodegenerative diseases

Abstract: Therapeutic strategies for regulating neuroinflammation are expected in the development of novel therapeutic agents to prevent the progression of central nervous system (CNS) pathologies. An understanding of the detailed molecular and cellular mechanisms of neuroinflammation in each CNS disease is necessary for the development of therapeutics. Since the brain is a sterile organ, neuroinflammation in Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS) is triggered by cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 101 publications
(98 reference statements)
1
15
0
Order By: Relevance
“…Both the EOfAD-like and fAI-like mutations caused very statistically significant changes in the gene sets KEGG_CYTOKINE_CYTOKINE_RECEPTOR _INTERACTION and KEGG_RIBOSOME. The former gene set reflects that both mutations appear to affect inflammation that is a characteristic of the pathologies of both EOfAD [93] and fAI (reviewed in [94]). Like oxidative phosphorylation, we have also observed effects on ribosomal protein genes sets for every EOfAD-like mutation we have studied [39][40][41]43].…”
Section: Discussionmentioning
confidence: 99%
“…Both the EOfAD-like and fAI-like mutations caused very statistically significant changes in the gene sets KEGG_CYTOKINE_CYTOKINE_RECEPTOR _INTERACTION and KEGG_RIBOSOME. The former gene set reflects that both mutations appear to affect inflammation that is a characteristic of the pathologies of both EOfAD [93] and fAI (reviewed in [94]). Like oxidative phosphorylation, we have also observed effects on ribosomal protein genes sets for every EOfAD-like mutation we have studied [39][40][41]43].…”
Section: Discussionmentioning
confidence: 99%
“…Brain aging is related to immunosenescence and low-grade inflammation (inflammaging), to which activated macrophages and monocytes will contribute and promote neuroinflammation, a key event in chronic age-related neurodegenerative diseases [ 524 , 525 ]. Similarly, systemic inflammation is also a predictor of brain aging [ 526 , 527 ].…”
Section: Apoe In Alzheimer’s Diseasementioning
confidence: 99%
“…Recent studies have shown that the disruption of the balance between anti-inflammatory and pro-inflammatory signals in the brain tissue of AD patients leads to chronic neuroinflammation, which is associated with activated microglia and the release of various cytokines ( Sonninen et al, 2020 ; Yang and Zhang, 2020 ). Persistent immune/inflammatory responses in the brain are not only associated with neuronal loss and neurodegeneration but are also closely related to the initial Aβ pathology and its interaction with NFTs ( Otani and Shichita, 2020 ). The pathological changes in Aβ and tau in the brain cause excessive activation of astrocytes and microglia, express a large number of inflammatory substances, and produce an excessively sustained chronic inflammatory response, which leads to neuronal dysfunction, degeneration, and apoptosis ( Calsolaro and Edison, 2016 ; Zhou et al, 2019 ).…”
Section: Pathological Features Of Alzheimer’s Diseasementioning
confidence: 99%